Safety in big jumps: relationship between landing shape and impact energy determined by computer simulation - Böhm, H.; Senner, V. (Skiing Trauma and Safety: 17th Volume, 2009)
With the increasing popularity of freestyle skiing and snowboarding many ski resorts constructed their own terrain parks including several jumps, rails, and pipes. In order to prevent risks of high-impact injuries in jumping, an adequate construction of the landing hill is very important. In professional ski jumping this can be achieved by designing the landing area profile so that its curvature follows the flight path of the jumping athlete. Classical kicker shapes do not follow this principle. They consist of a ramp subsequently followed by a flat table and a descending landing area. Construction of these kickers is commonly made by trial and error. To make the construction process safer and reduce unnecessary risks, a guideline for save kicker construction based on multiple simplifications of the real situation was published in the literature. The purpose of this study was to investigate how this guideline applies to the situation in a real kicker. Two skiers and three snowboarders performed a total of eleven jumps on one expert's kicker (table length 17 m, transition angle 20°, and kick-off height 2.5 m). Computer simulations, based on the take-off velocities of the eleven jumps measured, were used to calculate the impact energy during landing on different table lengths combined with different landing slopes. If the jumper fails to adjust take-off velocity to account for the shorter deck length, the sum of the impact energies of the simulated jumps will increase dramatically at table lengths smaller than 15 m combined with a landing steepness greater than 20. The predictions based on the guideline (16 m table length and 33° landing steepness) are within a safe region. The guideline is therefore applicable for the experts kicker investigated.